Long-term outcome and pre-interventional predictors for late intervention after uterine fibroid embolization. (April 2020) - D'hoore, Tom; Timmerman, Dirk; Laenen, Annouschka; Maleux, Geert
Abstract: Objectives: To assess the long-term freedom of surgical conversion after uterine fibroid embolization (UFE) and to define predictors for better clinical outcome. Additionally, the potential of pregnancy after UFE is assessed. Study design: Single-center retrospective cohort study including 190 patients who underwent UFE between 2001 and 2016. Data were obtained by postal questionnaire including symptom severity, late reintervention rate and post procedural fertility. Patient characteristics were extracted from the patients' electronic medical records. The cumulative rate of freedom from treatment failure was determined by Kaplan-Meier analysis. Cox regression models were used for univariate analyses of the association between patient preinterventional characteristics and late surgical conversion. Secondary outcome measures were patient specific predictors of treatment failure and evaluation of post-procedural fertility. Results: Long-term follow-up was available for a median of 6.1 years (range 1.2–15.2 y) in 95 out of 190 patients (50 %). Freedom from treatment failure showed a cumulative rate of 72.9 % after 10 years and stable until end of follow-up. A 63.8 % reduction in symptoms and a 23.3% increase in quality of life was found. Significant increase of treatment failure was found in patients with increasing pre-interventional uterine volume (p = 0.0003) or dominant fibroid volume (p = 0.0042); 9 out of 23 patients (39.13 %) with child-bearing wish became pregnant and conceived one or more children after UFE. Conclusion: UFE is associated with sustained long-term symptom control. Larger size uterus or dominant fibroma are correlated with higher late surgical conversion rate. Last, women can become pregnant and deliver after UFE.